MENINGKATKAN KECERDASAN MUSIK BERMAIN ANGKLUNG MELALUI MODEL PEMBELAJARAN ASYIK - Zariyatul Haristiyah; Sri Watini (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Children’s musical intelligence is need to be explored and develop for early childhood. The impact and influence of musical intelligence on children’s growth and development is so wide, but unfortunately this has not been taken seriously. Therefore, it is time for Early Chilhood Education Institutions to pay serious attention. This study aims to develop the ASYIK model in increasing early childhood musical intelligence through playing angklung. The method used in this research is classroom action research through qualitative data analysis by providing an achievement scale. The instruments used are observation, interviews and documentation. The Kindergarten Institution chosen was TK Yapis 1 Reremi Manokwari. The results of research and develompemt are based on effectiveness tests, so the ASYIK model is effective in increasing musical intelligence in kindergarten.